Maxillary constriction: are there differences between anterior and posterior regions? Atresia maxilar: há diferenças entre as regiões anterior e posterior? - Regina Helena Lourenço Belluzzo; Kurt Faltin Junior; Cícero Ermínio Lascala; Lucas Bacci Renno Vianna (Dental Press Editora, 2012)
OBJECTIVE: To evaluate the transverse constriction of the maxilla in both anterior and posterior regions, using Korkhaus analysis and to check whether there were any statistically significant differences within its values. METHOD: The sample comprised 341 study models. The study models were randomly selected from previous cases, without gender, age and malocclusion restrictions. The models were submitted to Korkhaus analysis. Data from these models were subjected to statistical analyzes in order to evaluate differences in anterior and posterior regions. RESULTS: The transverse discrepancies were statistically significant (p<0.001) with a greater constriction in the anterior region (mean -2.84 mm). CONCLUSION: The results showed that the differential diagnosis is very important and the treatment plan may be adapted to specific therapy focusing in a greater expansion in the anterior region. OBJETIVO: avaliar a atresia transversa da maxila em duas regiões anatômicas, anterior e posterior, através da análise de Korkhaus, e verificar se há diferença estatisticamente significativa em seus valores. MÉTODOS: a amostra foi constituída de 341 modelos de estudo iniciais, escolhidos aleatoriamente, sem restrições em relação ao sexo, à idade e à má oclusão. Os modelos foram submetidos à análise transversa de Korkhaus e os valores obtidos analisados estatisticamente, para avaliar se as atresias encontradas eram diferentes nas regiões anterior e posterior. RESULTADOS: as discrepâncias transversas são, em média, -2,84mm mais atrésicas na região anterior, sendo essa diferença estatisticamente significativa. CONCLUSÃO: os resultados mostraram que o diagnóstico diferencial é muito importante e devemos adequá-lo aos nossos planos de tratamento e, consequentemente, a uma terapia específica de expansão maior na região anterior.